Paciente de sexo masculino de 40 años de edad con diabetes mellitus tipo 2 con complicacion de pie diabetico, hipertension arterial, insufiencia renal cronica sometido a dialisis. - Rey Garces, Cristhian Fernando (2020)
The present clinical case is a mature adult of 54 years of age, with a personal history of type 2 diabetes mellitus, arterial hypertension and chronic renal failure which is submitted twice a week to dialysis, allergies does not refer, within the background Surgical indicates that two weeks ago he underwent a supracondylar amputation by diabetic foot, within the family pathology of parents who died of arterial hypertension; Patient comes by emergency for presenting a clinical picture of headaches, blurred vision, accompanied by tenesmus, polyakyria, dysuria; On physical examination head and thorax without novelty, edema does not present, rhythmic heart sounds with ventilated lung fields; Vital signs: Blood pressure 150/90 mmhg, heart rate, 76 beats per minute, respiratory rate 18 per minute, oxygen saturation 97% and body temperature 36.7 ° c; The nutritional assessment is carried out, including weight: 70 kg height: 162cm reflecting a BMI of 26.7kg / m2 overweight with increased cardiovascular risk; The corresponding biochemical tests were performed and reflected elevated hyperglycemia, creatinine, urea and BUN, and mild anemia, patient indicates that he is taking his medication as indicated by the endocrinologist, but does not make recommendations for diet or physical activity, so it is referred to the nutritionist for intervention. We proceed to perform the individualized nutritional intervention to the patient, taking into account important aspects such as the socioeconomic situation and its pathological condition; A normocaloric diet with hyperproteic, hyposodic, normoglucidal, normolipidic, high fiber characteristics, divided into 5 meal times will be prescribed. The objective of implementing a nutritional plan is to counteract the medication and avoid other complications in the future for the patient.